2022
DOI: 10.1186/s44158-022-00067-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of video-calls between patients admitted to intensive care unit during the COVID-19 pandemic and their families: a pilot study of psychological effects

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has caused over 530 million infections to date (June 2022), with a high percentage of intensive care unit (ICU) admissions. In this context, relatives have been restricted from visiting their loved ones admitted to hospital. This situation has led to an inevitable separation between patients and their families. Video communication could reduce the negative effects of such phenomenon, but the impact of this strategy on levels of anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In 19 studies, video calls were used for virtual visits between patients and families (Dainty et al, 2023;Dhahri et al, 2021;Dhala et al, 2020;Dürst et al, 2022;Ehrler et al, 2021;Kebapcı & Türkmen, 2022;Moolla et al, 2020;Moraes & Chiaradia Mendes-Castillo, 2023;Nicholas et al, 2011;Padua et al, 2021;Parsapour et al, 2011;Ranu et al, 2021;Rose et al, 2021;Rose, Cook, et al, 2022;Sanfilippo et al, 2022;Thomas et al, 2021;Wong & Merchant, 2021;Yang et al, 2014;Yuan et al, 2023), and between patients, families and healthcare professionals in 24 studies (Bansal et al, 2022;Bavare et al, 2021;Bettini, 2020;Carlucci et al, 2020;Cherniwchan, 2022;Chua, 2022;Conroy et al, 2021;de Havenon et al, 2015;Dol et al, 2017;Elma et al, 2022;Epstein et al, 2017;Galazzi et al, 2021;Giuseppe et al, 2022;Kennedy et al, 2021;Nelson et al, 2022;Otte et al, 2022;Rose et al, 2021;Rose, Graham, et al, 2022;Sasangohar et al, 2021;Shunker, 2022;Webb et al, 2020;…”
Section: Characteristics Of the Intervention Studiedmentioning
confidence: 99%
“…In 19 studies, video calls were used for virtual visits between patients and families (Dainty et al, 2023;Dhahri et al, 2021;Dhala et al, 2020;Dürst et al, 2022;Ehrler et al, 2021;Kebapcı & Türkmen, 2022;Moolla et al, 2020;Moraes & Chiaradia Mendes-Castillo, 2023;Nicholas et al, 2011;Padua et al, 2021;Parsapour et al, 2011;Ranu et al, 2021;Rose et al, 2021;Rose, Cook, et al, 2022;Sanfilippo et al, 2022;Thomas et al, 2021;Wong & Merchant, 2021;Yang et al, 2014;Yuan et al, 2023), and between patients, families and healthcare professionals in 24 studies (Bansal et al, 2022;Bavare et al, 2021;Bettini, 2020;Carlucci et al, 2020;Cherniwchan, 2022;Chua, 2022;Conroy et al, 2021;de Havenon et al, 2015;Dol et al, 2017;Elma et al, 2022;Epstein et al, 2017;Galazzi et al, 2021;Giuseppe et al, 2022;Kennedy et al, 2021;Nelson et al, 2022;Otte et al, 2022;Rose et al, 2021;Rose, Graham, et al, 2022;Sasangohar et al, 2021;Shunker, 2022;Webb et al, 2020;…”
Section: Characteristics Of the Intervention Studiedmentioning
confidence: 99%
“…Checklists when establishing contact with families by telephone or video were also used to share information. More recent studies reported the use of videoconferencing 16 or video calls 7,17 . Other methods to engage families were also found, such as the creation of liaison groups to encourage family engagement with health care teams, including ICU family liaison services, 16 family support teams, 8 or video diaries 18…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies reported the use of videoconferencing 16 or video calls. 7,17 Other methods to engage families were also found, such as the creation of liaison groups to encourage family engagement with health care teams, including ICU family liaison services, 16 family support teams, 8 or video diaries. 18 Some evidence points out that virtual communication between families and health care professionals in ICUs is a useful alternative to in-person meetings.…”
Section: Introductionmentioning
confidence: 99%